Sexual violence as an international crime: interdisciplinary approaches - Brouwer, Anne-Marie de; Ku, Charlotte; Römkens, Renée; Herik, Larissa J. van den (Series on transitional justice, 2013)
This edited volume focuses on developments in recognizing, investigating, and prosecuting cases of sexual violence in (post-)conflict situations from an interdisciplinary angle. The investigation and prosecution of these cases raises new and challenging questions as to how to build evidence, but also how to address victims’ concerns in that process. It addresses innovations and challenges of empirical and other new kinds of social scientific, archival and medical data collection techniques; the development of evidence in relation to charges ranging from sexual violence as a war crime, crime against humanity to genocide; evidentiary and procedural achievements and challenges involved in prosecuting sexual victimization in international courts; and how to create awareness of sexual violence crimes in order to recognize such crimes and to prevent them in the future.